THE LIMITS OF DISC: A CRITICAL EXAMINATION OF PSYCHOPATHY AND MANIPULATION IN POPULAR PERSONALITY PROFILES - BELAID, Louiza (Psychological thought, 2025)
From a psychological perspective, society functions as an intricate web of diverse personalities. Yet certain traits, such as emotional regulation, empathy, and moral awareness, are widely recognized as indicators of psychological health, transcending individual differences. This suggests that, despite people’s varied backgrounds and experiences, they share fundamental characteristics that define rational behavior. Similarly, there are complex personalities whose intentions transcend the scope of the DISC color model. The model’s neutral category may correspond to psychopathic traits, which are central to the clinical study of psychopathy. This article critically examines the personality profiles popularized by Thomas Erikson, a figure widely known in popular psychology, and explores specific techniques employed to counter manipulative behaviors. The review aims to promote self-awareness and interpersonal understanding by examining how manipulation tied to psychopathic behavior leads to emotional distress and self-destructive tendencies. The paper also sheds light on the forensic and ethical implications of applying pseudoscientific models in psychological and criminal assessment settings. To comprehensively evaluate psychopathy from Erikson’s perspective, the researcher selected both the English version and the Arabic translation to ensure that all essential components of psychopathy were reviewed.